Calcium ion‐induced self‐healing pattern of chemically crosslinked poly(acrylic acid) hydrogels. Issue 3 (16th January 2018) - Anjum, Sadiya; Gurave, Pramod M; Gupta, Bhuvanesh
Abstract : We have realized the design of novel poly(acrylic acid) (PAA)‐based self‐healing hydrogels by virtue of the incorporation of Ca 2+ ions within the hydrogel matrix which leads to the origin of self‐healing behaviour. Abstract: Poly(acrylic acid) hydrogels crosslinked with N, N ′‐methylenebisacrylamide were synthesized by free radical polymerization. Polymerization conditions had a significant influence over the gel content and swelling behaviour of the hydrogels. The incorporation of calcium ions led to the origin of a self‐healing feature. The self‐healing behaviour and mechanical performance of the hydrogels were systematically investigated. The hydrogels showed good tensile strength of 1 MPa and excellent stretchable behaviour where hydrogels regained instantaneously. Hydrogel pieces joined together to become an integrated matrix as soon as two cut pieces were brought in contact. The hydrogels possessed a marked healing efficiency of 97% within 6 h at room temperature without any external intervention. The results are explained in terms of the dynamic mobility of calcium ions within the dual‐crosslinked networks of the poly(acrylic acid) hydrogels. © 2017 Society of Chemical Industry